2008
DOI: 10.1111/j.1532-849x.2008.00366.x
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Evaluation of Fit of Zirconium‐Oxide‐Based Ceramic Four‐Unit Fixed Partial Dentures, Generated with Three Different CAD/CAM Systems, before and after Porcelain Firing Cycles and after Glaze Cycles

Abstract: Within the limitations of this study, it was concluded that the three zirconium-oxide-based ceramic CAD/CAM systems demonstrated a comparable and acceptable marginal fit; however, the Lava system produced gap measurements statistically smaller than the Everest and Procera systems. The porcelain firing cycles and the glaze cycles did not affect the marginal fit of the zirconium-oxide-based ceramic CAD/CAM systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
89
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(98 citation statements)
references
References 23 publications
(26 reference statements)
5
89
1
3
Order By: Relevance
“…This finding is supported by several studies on the effect of porcelain veneering on the accuracy of fit of zirconia restorations [12][13][14]26) . An exception was found with a study by Vigolo and Fonzi 15) , who reported that veneering did not affect the fitting accuracy of zirconia restorations.…”
Section: Strain Developmentmentioning
confidence: 76%
See 2 more Smart Citations
“…This finding is supported by several studies on the effect of porcelain veneering on the accuracy of fit of zirconia restorations [12][13][14]26) . An exception was found with a study by Vigolo and Fonzi 15) , who reported that veneering did not affect the fitting accuracy of zirconia restorations.…”
Section: Strain Developmentmentioning
confidence: 76%
“…Balkaya et al 14) found that only the porcelain firing cycle affected the marginal fit of all-ceramic single crowns, but not so with the glaze firing cycle. On the other hand, Vigolo and Fonzi 15) found that neither the porcelain firing cycle nor the glaze cycle affected the marginal fit of four-unit CAD/CAMfabricated zirconia restorations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the ceramic firing cycles and glaze 16) . On the other hand, Vigolo and Fonzi found that porcelain firing cycles and glazing cycles did not affect the marginal fit of the zirconium-oxide-based ceramic with three different CAD/CAM systems 17) . Marginal fit is one of the most important criteria for the long-term success of all-ceramic crowns 18) .…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that heat treatment influences the surface of the ceramic material by reducing the amount of monoclinic zirconia grains, which is suggested to result in a lower strength. Vigolo and Fonzi [14] found that the veneering porcelain firing cycle or the veneer glazing cycle did not affect the marginal fit of the fixed partial dentures. Whereas Dittmer et al found in a recent study that stresses and distortions that occur due to the veneering process may influence the marginal and internal fit of zirconia dental crowns and fixed partial dentures [15].…”
Section: Introductionmentioning
confidence: 99%